Preamplification Procedure for the Analysis of Ancient DNA Samples - Stefania Del Gaudio; Alessandra Cirillo; Giovanni Di Bernardo; Umberto Galderisi; Theodoros Thanassoulas; Theodoros Pitsios; Marilena Cipollaro (The Scientific World Journal)
In ancient DNA studies the low amount of endogenous DNA represents a limiting factor that often hampers the result achievement. In this study we extracted the DNA from nine human skeletal remains of different ages found in the Byzantine cemetery of Abdera Halkidiki and in the medieval cemetery of St. Spiridion in Rhodes (Greece). Real-time quantitative polymerase chain reaction (qPCR) was used to detect in the extracts the presence of PCR inhibitors and to estimate the DNA content. As mitochondrial DNA was detected in all samples, amplification of nuclear targets, as amelogenin and the polymorphism M470V of the transmembrane conductance regulator gene, yielded positive results in one case only. In an effort to improve amplification success, we applied, for the first time in ancient DNA, a preamplification strategy based on TaqMan PreAmp Master Mix. A comparison between results obtained from nonpreamplified and preamplified samples is reported. Our data, even if preliminary, show that the TaqMan PreAmp procedure may improve the sensitivity of qPCR analysis.